“Art’s Neurosis”: Medicine, Mass Culture and the Romantic Artist in William Hazlitt - Budge, Gavin (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractAlthough criticism has traditionally focussed on the Romantic celebration of artistic genius, there is also an emphasis on artistic abjection in Romantic writing. This essay argues that the Romantic theme of abjection is linked to the claims of early nineteenth-century Brunonian medicine that conditions of nervous over- and understimulation are the cause of diseases such as consumption and hypochondria, a case which is made with particular reference to the writings of William Hazlitt. Brunonian medical theory also informs Romantic period analyses of a newly emergent mass culture, enabling Romantic depictions of artistic abjection to be understood as a denial of the Romantic artist's involvement in a mediatization of experience which potentially distances the audience from the intuition of reality to which Romanticism ultimately appeals. This ambivalence about the position of the Romantic artist is reflected in the Romantic period debate surrounding the aesthetic category of the picturesque, which is shown to draw on Brunonian ideas about nervous stimulation in a way which makes it exemplary of conflicted Romantic attitudes towards the effects of mediatization.